C- and N-truncated antimicrobial peptides from LFampin 265 - 284: Biophysical versus microbiology results - Regina Adão (2011)
Lactoferrin is a glycoprotein with two globular lobes, each having two domains. Since the discovery of itsantimicrobial properties, efforts have been made to find peptides derived from this protein showing antimicrobialproperties. Most peptides initially studied were derived from Lactoferricin B, obtained from the protein bydigestion with pepsin. More recently, a new family of antimicrobial peptides (AMPs) derived from Lactoferrinwas discovered by Bolcher et al, and named Lactoferrampin (LFampin). The original sequence of LFampincontained residues 268 - 284 from the N1 domain of Lactoferrin. From this peptide, the Bolscher's groupsynthesized a collection of peptides obtained by extension and / or truncation at the C or N-terminal sides,in order to unravel the main structural features responsible for antimicrobial action. Here, we present resultsfor three of these peptides, namely LFampin 265 - 284, LFampin 265 - 280, and LFampin 270 - 284. Thepeptides were tested against bacteria (E. coli and S. sanguinis), fungi (C. albicans), and model membranes of1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC), 1,2-dimyristoyl-sn-glycero-3-[phospho-rac-(1-glycerol)](DMPG), and their mixtures at a ratio of 3 : 1 (DMPC : DMPG (3 : 1)). The ability to adopt a helical conformationwas followed by a circular dichroism (CD), and the perturbation of the gel to the liquid-crystalline phasetransition of the membrane was characterized by differential scanning calorimetry (DSC). Distinct behaviorwas observed in the three peptides, both from the microbiology and model membrane studies, with thebiophysical results showing excellent correlation with the microbiology activity studies. LFampin 265 - 284was the most active peptide toward the tested microorganisms, and in the biophysical studies it showed thehighest ability to form an α-helix and the strongest interaction with model membranes, followed by LFampin265 - 280. LFampin 270 - 284 was inactive, showing marginal secondary structure and no interaction withthe pathogen model membranes.